Study on IL-2 and CA 15-3 level as combined biomarkers in monitoring chemotherapeutic response among invasive breast cancer patients - Abdul Hameed, Ahmed Muthanna; Abdul Hamid, Auni Fatin; Noor, Nurul Shahfiza; Appalanaido, Gokula Kumar; Sahul Hamid, Shahrul Bariyah (IOP Publishing, 2017)
In Malaysia, breast cancer is the most frequent type of disease among women. This study was designed to determine the clinical usefulness of carbohydrate antigen (CA 15-3) and interleukin 2 (IL-2) levels as combined biomarkers in monitoring breast cancer patient’s response to chemotherapy. Ethical approval was obtained to recruit patients with histologically confirmed invasive ductal carcinoma (IDC) attending Oncology Clinic at Advanced Medical and Dental Institute. Whole blood was collected from 10 IDC breast cancer patients’ pre and post primary chemotherapy. Plasma was separated from the whole blood to determine the CA 15-3 level and IL-2 level using enzyme-linked immunosorbent assay (ELISA) pre and posttreatment. In addition, the histological findings, tumour stage and other patients’ data were obtained from the medical record. Findings showed that IL-2 had borderline significant changes between pre- and post-chemotherapy (p = 0.074) whereas for CA 15-3, there was insignificant differences of CA 15-3 level between pre and post-chemotherapy (p > 0.05). It was noted that only CA 15-3 level had significant correlation with tumour size. This study demonstrates that IL-2 level requires further investigation in a larger sample size to correlate its potential use as combined biomarker with CA 15-3 in monitoring response to chemotherapy.